2013
DOI: 10.11114/jets.v1i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Gender and Student Performance in Mathematics. Evidence from Catalonia (Spain)

Abstract: This paper analyses the impact of teacher gender towards students' test results in a blinded Math test administered to students in Catalonia (Spain). The data for this analysis are drawn from a sample of secondary school students who participated in an international blind-test known as the "Mathematical Kangaroo" in 2008. The estimation considers a two-stage procedure since participation on the test leads to the presence of sample selection. Results show a correlation between female teacher gender and student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Empirical evidence resulting from research in this field, as showed by Escardibul and Mora (2013), point out that an accurate determination of the relationship between gender of teachers and student achievement in primary and secondary education is yet to be established. It is prudent to consider that our objective was to analyze the best hierarchical model that may substantiate political policies aiming to improve the achievement of students in Portuguese and Mathematics, and not focused on exploring the determinants of gender influence of teachers on the achievement of students.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence resulting from research in this field, as showed by Escardibul and Mora (2013), point out that an accurate determination of the relationship between gender of teachers and student achievement in primary and secondary education is yet to be established. It is prudent to consider that our objective was to analyze the best hierarchical model that may substantiate political policies aiming to improve the achievement of students in Portuguese and Mathematics, and not focused on exploring the determinants of gender influence of teachers on the achievement of students.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies do not find significant differences in the effect of male and female teachers and, when a significant difference is found, it is in favour of female teachers (see Escardíbul and Mora 2013). The significant effect in favour of male teachers that appears in our estimation is, therefore, an unexpected result and one which should be explored in further studies, in order to verify whether there is any relation with any specific feature of the Spanish education system.…”
Section: Model Estimation Resultsmentioning
confidence: 56%
“…Indeed, policies have been implemented in several English-speaking countries to increase the participation of men, currently in a minority, among teaching staff (Carrington et al 2007(Carrington et al , 2008. However, there is no conclusive empirical evidence to show that male teachers are better than female teachers; moreover, in studies in which the gender variable is significant, the results suggest students benefit from having a female teacher (for a review of such studies, see Escardíbul and Mora 2013).…”
Section: Empirical Evidence Of the Relevance Of Teachers In Students'...mentioning
confidence: 99%
“…• The second group of factors includes teacher characteristics. The individual components of this group are age (Mohammadpour, 2012), gender (EscardĆbul, & Mora, 2013), experience (Maat, Zakaria, Nordin, & Meerah, 2011;Eshiwani, 2001), teaching methods (Damrongpanit, 2019), assessment practices (Liang, 2010), classroom management (Van Dijk, Gage, & Grasley-Boy, 2019), student collaboration in mathematics classes , teacher behavior (Den Brok, Brekelmans, & Wubbels, 2004), and homework allocation (Fernández-Alonso, Álvarez-Díaz, Suárez-Álvarez, & Muñiz, 2017). Farooq, Chaudhry, Shafiq, & Berhanu, 2011), parental involvement in terms of homework assistance, home supervision, educational expectations for children (Wilder, 2014), family socioeconomic status (Kiwanuka, Van Damme, Van Den Noortgate, Anumendem, & Namusisi, 2015;Wang, Li, & Li, 2014;Liang, 2010;Sirin, 2005), family cultural background (Thien, & Ong, 2015;Liang, 2010), and family obligations that might weight on children (Kim, & Chung, 2012).…”
Section: The Conceptual Framework Of the Studymentioning
confidence: 99%